Sensitivity of the response of thick cross-ply doubly curved panels to edge clamping - Oktem, Ahmet Sinan; Chaudhuri, Reaz A. (ELSEVIER SCI LTD, 2009)
A heretofore unavailable analytical solution to the problem of deformation of a finite-dimensional general cross-ply thick doubly-curved panel of rectangular plan-form, modeled using a higher order shear deformation theory (HSDT), is presented. A solution methodology, based on a boundary-discontinuous generalized double Fourier series approach, is used to solve a system of five highly coupled linear partial differential equations, generated by the HSDT-based laminated shell analysis, with the C3-type clamped boundary condition prescribed at all four edges. The numerical accuracy of the solution is ascertained by studying the convergence characteristics of deflections and moments of a cross-ply spherical panel. The primary focus of the present study is to investigate the effect of edge clamping on the response of a thick laminated doubly-curved panel, while keeping the surface-parallel edge constraints unaltered. Important numerical results presented include sensitivity of the predicted response quantities of interest to lamination, material property, thickness and curvature effects, and edge clamping as well as their interactions. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Thick cross-ply laminate; Higher order shear deformation theory (HSDT); Spherical shell; Cylindrical shell; Boundary discontinuous double fourier series; Edge clamping; DISCONTINUOUS FOURIER-ANALYSIS; BOUNDARY-VALUE-PROBLEMS; HIGHER-ORDER THEORY; MODERATELY-THICK; FREE-VIBRATION; FREQUENCY-RESPONSE; SHELL; CONSTRAINT; DEFORMATION; SERIES; Mechanics; Materials Science